Davitskebuli Portreti Interiershi - Kuntsev-Gabashvili, Vakhtang (Georgia : Akrobat, 2006)
A documentary about the life and works of French actress Simone Signoret.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films